New insights into the interfacial behavior and swelling of polymer inclusion membrane (PIM) during Zn (II) extraction process. (20th July 2020) - Wang, Duo; Liu, Jing; Chen, Jingsi; Liu, Qi; Zeng, Hongbo
Graphical abstract: Schematic diagram of Zn (II) extraction process in polymer inclusion membrane (PIM) system at macroscopic and microscopic levels. Highlights: A model PIM (D2EHPA and PVDF-HFP) was made to extract Zn(II) from ZnSO4 solution. Real-time behaviors at PIM/aqueous-environment interface were monitored by QCM-D. Introducing aqueous environment to PIM induces water penetration into membrane. PIM layer responds differently to various concentrations of Zn(II) in feed solution. Higher Zn(II) concentration renders more remarkable membrane swelling in PIM layer. Abstract: Polymer inclusion membrane (PIM) has been progressively utilised in various chemical engineering applications. Understanding the interfacial interactions between PIM surface and surrounding solutions is significantly important for the industrial application of PIM systems. In this work, interfacial behavior of the PIM was studied during Zn(II) extraction process. The real-time change of the PIM under various environmental conditions was monitored by Quartz crystal microbalance with dissipation monitoring. Water penetration into the PIM layer was demonstrated when the PIM was in contact with Milli-Q water. Atomic force microscopy imaging confirmed that the swollen PIM had a looser network and rougher surface, as compared to its original state. When switching the surrounding environment to ZnSO4 solution, higher Zn(II) concentration could induce microstructure change and more significant membrane swelling in the PIM layer. Our results provide valuable implications for the design of effective PIM systems towards practical applications in wastewater treatment and hydrometallurgy.